2012
DOI: 10.3732/ajb.1200062
|View full text |Cite
|
Sign up to set email alerts
|

The leaf‐area shrinkage effect can bias paleoclimate and ecology research

Abstract: Our findings indicate that the amount of shrinkage is driven by variation in leaf area, leaf thickness, evergreenness, and woodiness and can be reversed by rehydration. The amount of shrinkage may also be a useful trait related to ecologically and physiological differences in drought tolerance and plant life history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 41 publications
3
48
1
1
Order By: Relevance
“…S4). This effect is of similar magnitude to the shrinkage reported in rehydrated leaves by Blonder et al (2012). Our observation that VLA in eucalypts increases with increasing aridity is in line with the global compilation of vein density data by Sack and Scoffoni (2013), who show a strong correlation between VLA and aridity across biomes.…”
Section: Discussionsupporting
confidence: 91%
“…S4). This effect is of similar magnitude to the shrinkage reported in rehydrated leaves by Blonder et al (2012). Our observation that VLA in eucalypts increases with increasing aridity is in line with the global compilation of vein density data by Sack and Scoffoni (2013), who show a strong correlation between VLA and aridity across biomes.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, a recent study quantified PLA dry in 380 diverse species (Blonder et al, 2012) and found PLA dry to be slightly higher for dry habitat species, although that trend may have arisen due to error in the measurements. In that study, PLA dry was determined without first rehydrating the leaves to full turgidity, and erroneous negative PLA dry data were included in that study.…”
Section: Applications Of Leaf Shrinkage For Drought Monitoring and Drmentioning
confidence: 99%
“…Leaves shrink in their area (Bogue, 1892;Gardner and Ehlig, 1965;Jones, 1973;Tang and Boyer, 2007;Blonder et al, 2012) and, considered in relative terms, even more strongly in their thickness (Fig. 1;Meidner, 1952;Gardner and Ehlig, 1965;Downey and Miller, 1971;Syvertsen and Levy, 1982;Saini and Rathore, 1983;Burquez, 1987;McBurney, 1992;Sancho-Knapik et al, 2010.…”
mentioning
confidence: 99%
“…Large size also may be due to preservational factors, specifically the rapid fossilization that accompanies preservation of organic matter in ironstones (Laveine, 1990) preventing significant shrinkage; Cleal and Shute (2007) discuss this specifically with regard to Mazon Creek fossils, noting that this is probably not the explanation, given the extremely large size of many of the specimens from that flora. In addition, a study of leaf shrinkage (Blonder et al, 2012) indicates that preservation of leaves in mud prevents most shrinkage, as does rehydration of dried leaves. Thus, shrinkage should be an issue only if specimens were exposed to severe dehydration before being buried rapidly, without sufficient opportunity to rehydrate.…”
Section: Division Tracheophyta Class Spermatopsidamentioning
confidence: 99%